Charlando : a conversational approach to beginning Spanish - Inman, Sys Strandnes (New York : Holt, Rinehart, and Winston, 1988)
Charlando reduces the grammatical syllabus to a practical and achievable level.
Includes index.
Keywords: SPANISH LANGUAGE -- CONVERSATION AND PHRASE BOOKS -- ENGLISH; SPANISH LANGUAGE -- TEXTBOOKS FOR FOREIGN SPEAKERS -- ENGLISH; SPANISH LANGUAGE